1988
DOI: 10.1002/art.1780310805
|View full text |Cite
|
Sign up to set email alerts
|

Sex hormone status and osteoporosis in postmenopausal women with rheumatoid arthritis

Abstract: Sex hormones have important effects on bone, especially in postmenopausal women. These hormones may be of particular significance in patients with rheumatoid arthritis (RA), who have a high frequency of osteoporosis. To examine this, we measured estrogen and androgen concentrations and bone mineral density (BMD) in 49 postmenopausal women with RA and 49 normal postmenopausal women. Compared with the controls, postmenopausal RA patients had significantly reduced levels of estrone (median 18 pmoleslliter versus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
3

Year Published

1990
1990
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(48 citation statements)
references
References 19 publications
1
44
0
3
Order By: Relevance
“…We discovered that women with pSS, sSS + SLE, and sSS + RA are androgen deficient [4]. Similarly, others have found that pSS [48], as well as SLE and RA [49-57], are associated with a significant decrease in serum levels of androgen precursors (i.e., DHEA [dehydroepiandrosterone] and DHEA sulfate). These circulating precursors are the primary substrate for androgen synthesis in peripheral tissues, and this intracrine production generates the vast majority of androgens in women [58, 59].…”
Section: Discussionmentioning
confidence: 99%
“…We discovered that women with pSS, sSS + SLE, and sSS + RA are androgen deficient [4]. Similarly, others have found that pSS [48], as well as SLE and RA [49-57], are associated with a significant decrease in serum levels of androgen precursors (i.e., DHEA [dehydroepiandrosterone] and DHEA sulfate). These circulating precursors are the primary substrate for androgen synthesis in peripheral tissues, and this intracrine production generates the vast majority of androgens in women [58, 59].…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in serum levels of dehydroepiandrosterone sulfate (DHEAS) and DHEA is typical for noninfectious chronic inflammation where TNF and IL-6 have a predictive role for such changes 30,31 as in autoimmune disorders, including inflammatory bowel disease, 32 rheumatoid arthritis, 33,34 systemic lupus erythematosus, 35 and pemphigus. 36 These low levels are also seen in infectious diseases with chronic inflammation, such as tuberculosis, where DHEA prevents experimental infection in mice when given within the first few days or before M. tuberculosis inoculum.…”
Section: Patientsmentioning
confidence: 99%
“…Corticosteroids impair bone formation directly through the inhibition of osteoblast activity [112] and indirectly by decreasing sex steroid secretion [113], decreasing intestinal calcium absorption [114], increasing urinary calcium excretion [115] and promoting bone resorption due to secondary hyperparathyroidism [116]. Prevention of corticosteroid-induced osteoporosis can be primary, at the onset of corticosteroid therapy, or secondary, after low bone density has developed.…”
Section: Vitamin D and Drug Therapymentioning
confidence: 99%